Determinants of wasteful food consumption behaviors of young consumers in Ho Chi Minh City - Nong , Thi Nhu Mai; Tran, Nguyen Tuong Vy; Tran , Nguyen Truc My; Tran , Thi Thuy Trang; Tran, Phuc Bao Tran; Mai , Dang Phuc (Journal of Finance - Marketing Research, 2025)
Food waste is a serious global issue with multidimensional economic, environmental, and social consequences. In major urban centers such as Ho Chi Minh City, this behavior is increasingly prevalent, particularly among young consumers (aged 18-35), causing significant resource losses and affecting sustainable development. The study utilizes an exploratory sequential mixed-methods approach, including a qualitative phase through focus group discussions with experts and young consumers, followed by a quantitative phase with data collected from an online survey of 338 young people living and working in Ho Chi Minh City. Research results indicate that factors such as personal values have a positive impact on the attitude towards avoiding food waste. The results indicate a clear behavioral path: attitude, subjective norm, perceived behavioral control, and affect all significantly shape the intention to waste food. This intention, together with habit, then positively influences the actual food waste behavior. Notably, habit plays a prominent role in shaping actual behavior. These findings not only contribute to expanding the understanding of behavioral theoretical models but also provide an important empirical basis for designing communication programs, educational policies, and behavioral interventions aimed at raising awareness, changing habits, and promoting more responsible food consumption among the young urban community.